Chromatofocusing: a new method for purification of staphylococcal enterotoxins B and C1. - Ende, I A (1983)
A new chromatographic procedure was developed which obtained highly purified preparations of staphylococcal enterotoxins B and C1 in yields of 60% from cultures of Staphylococcus aureus and which is faster than any of the separation methods used previously. The procedure involves chromatography on carboxymethylcellulose, removal of alpha-toxin by adsorption to rabbit erythrocyte membranes, and finally, chromatofocusing as the fundamental new step. Enterotoxins were obtained in highly purified form and behaved in a homogeneous manner as determined by ultracentrifugation and electrophoresis on polyacrylamide gel in the presence of sodium dodecyl sulfate, with molecular weights of 34,000 for staphylococcal enterotoxin B and 30,000 for staphylococcal enterotoxin C1. Using chromatofocusing as the final purification step, we isolated three B and six C1 distinct but immunologically identical enterotoxin fractions, which were found to be devoid of any impurities and to possess a marked degree of toxicity in monkeys.